2021
DOI: 10.3390/jcm10040743
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of autologous Expanded Mesenchymal Stromal Cells in Hip Osteonecrosis through Percutaneous Forage: Evaluation of the Operative Technique

Abstract: Bone forage to treat early osteonecrosis of the femoral head (ONFH) has evolved as the channel to percutaneously deliver cell therapy into the femoral head. However, its efficacy is variable and the drivers towards higher efficacy are currently unknown. The aim of this study was to evaluate the forage technique and correlate it with the efficacy to heal ONFH in a multicentric, multinational clinical trial to implant autologous mesenchymal stromal cells expanded from bone marrow (BM-hMSCs). Methods: In the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…This would suggest that residual cysts may remain more frequently in the anterior region, which is consistent with Baba et al 39 who found a high bone-resorptive volume in the anterior femoral head of resected hips. A recommendation to aim the injection at the anterior femoral head, as previously suggested, 28 could be supported by this finding.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This would suggest that residual cysts may remain more frequently in the anterior region, which is consistent with Baba et al 39 who found a high bone-resorptive volume in the anterior femoral head of resected hips. A recommendation to aim the injection at the anterior femoral head, as previously suggested, 28 could be supported by this finding.…”
Section: Discussionsupporting
confidence: 73%
“…A third limitation is surgery and the injection placement of the cell therapy product, as analyzed in a recent paper. 28 However, the current study confirms that regeneration may extend in different areas of the femoral head lesion. Other aspects (tissue density and permeability, cell distribution after injection, cell progression, or survival within the lesion) may apply to explain variable bone regeneration.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…To avoid ONFH progression and eventual collapse of the femoral head, core decompression (CD) is considered to be the gold standard for all precollaptic stages 1,3,4 . In case of progressed ONFH, CD is augmented with bonemarrow injection, autologous bone grafting (ABG), or femoral osteotomy 3,[5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%